Advances in the differential molecular diagnosis of vesicular disease pathogens in swine - Chen, Wenxian; Wang, Weijun; Wang, Xinyan; Li, Zhaoyao; Wu, Keke; Li, Xiaowen; Li, Yuwan; Yi, Lin; Zhao, Mingqiu; Ding, Hongxing; Fan, Shuangqi; Chen, Jinding (Frontiers in Microbiology, 2022)
Foot-and-mouth disease virus (FMDV), Senecavirus A (SVA) and swine vesicular disease virus (SVDV) are members of the family Picornaviridae, which can cause similar symptoms -- vesicular lesions in the tissues of the mouth, nose, feet, skin and mucous membrane of animals. Rapid and accurate diagnosis of these viruses allows for control measures to prevent the spread of these diseases. RT-PCR and real-time RT-PCR are traditional and reliable methods for pathogen detection, while their amplification reaction requires thermocycler. Isothermal amplification methods including loop-mediated isothermal amplification (LAMP) and recombinase polymerase amplification (RPA) developed in recent years are simple, rapid and do not require specialized equipment, allowing for point of care diagnostics. Luminex technology allows for simultaneous detection of multiple pathogens. CRISPR-Cas diagnostic systems also emerging nucleic acid detection technologies which are very sensitivity and specificity. In this paper, various nucleic acid detection methods aimed at vesicular disease pathogens in swine (including FMDV, SVA and SVDV) are summarized.